Overview of equipment maintenance support mission planning model and solution - YANG Liangliang, ZHAO Deyong, LIU Xiaoyong, LIU Jie, SHEN Zixuan (Zhihui kongzhi yu fangzhen)
Our military’s exploration of equipment support mission planning is still in its infancy, traditional methods are difficult to meet the current equipment support needs, and there is an urgent need to combine with intelligent algorithms, machine learning and other new technology means to complete the support mission. Three typical multi-objective optimization models of equipment maintenance support mission planning were summarized and studied on the basis of analyzing the characteristics and content process of internal law of equipment maintenance support mission planning. The research status of the optimization model of maintenance demand estimation and force formation, maintenance mission assignment optimization model, maintenance job scheduling optimization model, and the solutions of the heuristic solution and mixed intelligent solution methods were summarized. Finally, a research outlook on intelligent mission planning for equipment maintenance support is presented.